2009
DOI: 10.1063/1.3197064
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the transport and thermoelectric properties of In2O3 bulk ceramics through doping at In-site

Abstract: Bulk ceramics In2−xMxO3, with a metal-like behavior, have been synthesized in air for M=Ti4+, Zr4+, Sn4+, Ta5+, and Nb5+, with rather low solubility limits xℓ, ranging from 0.01 to 0.1. An abrupt increase in the electrical conductivity and of the carrier concentration with x is observed in the monophasic region (x<xℓ), whereas in the biphasic region (x>xℓ) these values do not vary significantly. These results show that the valence of the doping element plays a crucial role in such properties, sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 14 publications
7
99
0
2
Order By: Relevance
“…It can be seen that as a result of these studies, that it was possible to substantially increase the ZT of n-type oxides. However, devices based on n-type conductive metal oxides have until now had a low efficiency of thermoelectric conversion [28,31,[38][39][40]42,70,71], which made their utilization in thermoelectric generators economically unprofitable. The demand for a good n-type thermoelectric oxide proceeds from the fact that it usually is being utilized as a partner for a p-type material in thermoelectric modules.…”
Section: Increase In Operating Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen that as a result of these studies, that it was possible to substantially increase the ZT of n-type oxides. However, devices based on n-type conductive metal oxides have until now had a low efficiency of thermoelectric conversion [28,31,[38][39][40]42,70,71], which made their utilization in thermoelectric generators economically unprofitable. The demand for a good n-type thermoelectric oxide proceeds from the fact that it usually is being utilized as a partner for a p-type material in thermoelectric modules.…”
Section: Increase In Operating Temperaturesmentioning
confidence: 99%
“…The experiment showed that various doping additives such as Sn [143][144][145], Ti [71], Zr [146,147], Mo [148], W [149] and Ge [70] can be used for these purposes. It is important to note here that with such doping it is possible to reach an exceptionally high carrier mobility in In 2 O 3 -based oxides even with a carrier concentration higher than 10 20 cm −3 (see Table 1).…”
Section: Electrophysical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some theoretical [13] and experimental work about the thermoelectric properties of In 2 O 3 and its dopants [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18] . There is work [5][6][7][8][9][10] about In 2 O 3 bulk and its dopant. For example, J. Lan et al studied the thermoelectric properties of In 2 O 3 codoped with Zn and Ge [5].…”
Section: Introductionmentioning
confidence: 99%
“…A typical approach to achieve certain functional properties is to stabilize a preferred polymorph and/or control its defect chemistry. [1][2][3] Research Centre were employed (Fig. 2).…”
mentioning
confidence: 99%